PENANGANAN KASUS PENCURIAN HEWAN TERNAK SAPI DI SP1 KABUPATEN SORONG OLEH POLRES AIMAS - naja, aufi; Salam, Muhammad Badrus (Muadalah : Jurnal Hukum, 2023)
The phenomenon of cattle theft in SP1 is increasingly disturbing the community, especially cattle breeders, because cattle breeders often experience the loss of their livestock which they suspect has been stolen by someone else. The research location is SP1 Sorong Regency. The research location is a location where cases of cattle loss often occur. Research is expected to obtain the information that researchers expect. The issue raised is about the reasons why the heirs are reluctant to receive the share they should receive. And at the Darul Falah Jekulo Kudus Islamic Boarding School to obtain information in the form of the opinion of the Kiyai or Pondok Caretaker regarding the issues raised.